Pengaruh Pengungkapan Emisi Karbon Dan Green Investment Terhadap Nilai Perusahaan - Astuti, Intan Novia; Ridha, Ainul; Eliana, Eliana (Jurnal Riset Akuntansi dan Bisnis, 2025)
This study aims to determine and analyze the effect of carbon emission disclosure and green investment on company value. The population in this study were energy sub-sector companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023. The sampling technique in this study used a purposive sampling method, resulting in 28 companies as research samples. The type of data used was secondary data, and the hypothesis testing method used multiple linear regression analysis with the Multiple Linear Regression Analysis technique. The results of this study indicate that the variables of carbon emission disclosure and green innovation influence company value.